Natrum muriaticum attenuates NaCl stress in Capsicum annuum L. var. glabriusculum - Rodríguez-Álvarez, Margarito; Morales-Roblero, Nehemías; Batista-Sánchez, Daulemys; Mazón-Suástegui, José Manuel (REVISTA TERRA LATINOAMERICANA, 2020)
Soil salinity is a global problem that increases year by year in arid and semi-arid regions, including Mexico where the distribution and extension of salinized soils reduces productivity and causes severe damage to different cultivated species. Homeopathic medicine is compatible with traditional, ecologic, and organic agriculture, and it can increase tolerance to salinity stress conditions and improve soil-plant ratio. Chiltepin chili (Capsicum annuum L. var. glabriusculum) is a species of high commercial value in northern Mexico affected by soil salinity. Thus, the objective of this study was to assess the eff iciency of Natrum muriaticum (NaM) homeopathic medicine for human use, to mitigate NaCl stress in chiltepin chili established in a hydroponic system and subjected to different NaCl concentrations. A completely randomized design (2A × 3B) with factorial arrangement was used with four replicates of nine plants each. The plants were subjected to two NaCl (0 and 200 mM) concentrations, two centesimal NaM (7CH and 13CH) of NaM (NaM-7CH and NaM-13CH) dynamizations and a control treatment without NaM. The variables evaluated were length, aerial and root part fresh and dry weight, leaf area, chlorophyll A, B, total relative water content, and water potential. In general, the plants treated with NaM-13CH showed the highest values for the majority of the morphometric and physiological variables, including the plants subjected to high salinity stress by adding NaCl (200 mM). These results conf irmed that NaM attenuated NaCl stress in chiltepin chili (C. annuum L. var. glabriusculum) plants and that agricultural homeopathy has the potential to increase productivity and yield in hydroponic cultivation of the species.